DNA Mismatch Repair-dependent Activation of c-Abl/p73α/GADD45α-mediated Apoptosis - Li, Long Shan (American Society for Biochemistry and Molecular Biology, 2008)
Cells with functional DNA mismatch repair (MMR) stimulate G(2) cell cycle checkpoint arrest and apoptosis in response to N-methyl-N′-nitro-N-nitrosoguanidine (MNNG). MMR-deficient cells fail to detect MNNG-induced DNA damage, resulting in the survival of “mutator” cells. The retrograde (nucleus-to-cytoplasm) signaling that initiates MMR-dependent G(2) arrest and cell death remains undefined. Since MMR-dependent phosphorylation and stabilization of p53 were noted, we investigated its role(s) in G(2) arrest and apoptosis. Loss of p53 function by E6 expression, dominant-negative p53, or stable p53 knockdown failed to prevent MMR-dependent G(2) arrest, apoptosis, or lethality. MMR-dependent c-Abl-mediated p73α and GADD45α protein up-regulation after MNNG exposure prompted us to examine c-Abl/p73α/GADD45α signaling in cell death responses. STI571 (Gleevec™, a c-Abl tyrosine kinase inhibitor) and stable c-Abl, p73α, and GADD45α knockdown prevented MMR-dependent apoptosis. Interestingly, stable p73α knockdown blocked MMR-dependent apoptosis, but not G(2) arrest, thereby uncoupling G(2) arrest from lethality. Thus, MMR-dependent intrinsic apoptosis is p53-independent, but stimulated by hMLH1/c-Abl/p73α/GADD45α retrograde signaling.